1993
DOI: 10.1093/eurheartj/14.suppl_c.18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of angiotensin converting enzyme inhibition on exercise performance and clinical symptoms in chronic heart failure: a multicentre, double-blind, placebo-controlled trial

Abstract: One hundred and seven patients with chronic heart failure (NYHA class II to IV) stabilized on digitalis and/or diuretics, recruited from 11 centres were randomized into a double-blind, placebo-controlled study to assess the effect of 12 weeks of cilazapril therapy on exercise tolerance and clinical status. Thirty-five patients were randomized to placebo and 72 to cilazapril at a starting dose of 1 mg daily; titration to cilazapril 2.5 mg at week 4 and 5 mg at week 8 (or matching placebo) was carried out in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Because of missing information on allocation concealment it was not possible to score for study quality properly. However, these 13 studies were large multi‐centre double blind parallel group trials [7,8,12–16,29,3135] wherein the allocation concealment might be considered adequate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of missing information on allocation concealment it was not possible to score for study quality properly. However, these 13 studies were large multi‐centre double blind parallel group trials [7,8,12–16,29,3135] wherein the allocation concealment might be considered adequate.…”
Section: Methodsmentioning
confidence: 99%
“…We chose the random‐effects model for continuous data, which provides the weighted mean difference with 95% confidence interval. All values presented as standard error of mean in the original studies [29,31,34] were recalculated to their standard deviations. In case of unreported standard deviations in the post‐treatment values the pre‐treatment values were substituted [7,8,12,30].…”
Section: Methodsmentioning
confidence: 99%
“…In heart failure, calcium 55 antagonists generally increase renin-angiotensin and sympathetic nervous system activity.42 It is unclear whether newer dihydropiridine calcium antagonists have a similar effect on these systems.…”
Section: Calcium Antagonistsmentioning
confidence: 99%
“…Observational studies have shown that the long-term use of ACE inhibitors was associated with a lower decline in muscle strength and walking speed in older hypertensive people and a greater lower limb lean muscle mass when compared with users of other antihypertensive agents. 110,111 Several studies have shown that ACE inhibitors improved exercise capacity in younger people with heart failure and this was also confirmed in older people with heart failure, 110,112,113 no improvement in grip strength. 114 Although this could be largely attributed to improvements in cardiac function, skeletal muscle atrophy is also associated with chronic heart failure so the evidence in muscle gains should not be discounted.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 94%